ANALISIS PENGARUH KUALITAS PELAYANAN, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN GRABFOOD DI KOTA BOYOLALI - Zahro Maftuhah Hasanah; Titin Hargyatni (LPPM Politeknik Pratama, 2022)
The results of multiple linear regression analysis obtained the equation Y = -1.824 + 0.595X1 + 0.471X2 + 0.268X3. The t-test analysis of the results for t-count service quality is 8,194 > ttable 1,986, so there is a positive and significant influence on the purchasing decision of Grabfood Online in Boyolali City. Analysis of the t-test results for t-count prices of 8.313 > ttable 1.986, then there is a positive and significant effect of the variable on the purchasing decision of Grabfood in Boyolali City. The t-test analysis obtained for t-count Promotion is 4,394 > ttable 1,986, so there is a positive and significant effect of promotion variables on Grabfood purchasing decisions in Boyolali City. Based on the analysis of the F test, the results obtained for the magnitude of the calculated F of 108,491 > F table 2,311, then together there is a significant influence between independent. Variables of Service Quality, Promotional Prices, To Purchase Decisions for Grabfood in Boyolali City. There is an influence between variables, namely Service Quality, Price, Promotion, Grabfood purchasing decisions in Boyolali City by 76.5%, while 23.5% is influenced by other factors that are not examined on customer satisfaction, customer loyalty, image or brand.